2023
DOI: 10.3390/plants12162944
|View full text |Cite
|
Sign up to set email alerts
|

New Insights into the Latest Advancement in α-Amylase Inhibitors of Plant Origin with Anti-Diabetic Effects

Abstract: The rising predominance of type 2 diabetes, combined with the poor medical effects seen with commercially available anti-diabetic medications, has motivated the development of innovative treatment approaches for regulating postprandial glucose levels. Natural carbohydrate digestion enzyme inhibitors might be a viable option for blocking dietary carbohydrate absorption with fewer side effects than manufactured medicines. Alpha-amylase is a metalloenzyme that facilitates digestion by breaking down polysaccharide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
17
1

Year Published

2024
2024
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 181 publications
(179 reference statements)
0
17
1
Order By: Relevance
“…Methanolic extracts of Vernonia antihelmitica callus and leaf showed an IC 50 of 0.499 mg/L and 0.372 mg/L, respectively(Rajan et al, 2022). Moderate inhibition (30-50%) of α-amylase is desired since excessive bacterial fermentation of non-digested carbohydrates in colon could cause diarrhea and atulence(Kashtoh & Baek, 2023).Contrasting to the α-amylase activities described above, no enzymatic inhibition was observed for αglucosidase (data not shown). A previous study carried out by Cuevas-Juárez et al(2014), reported that partially puri ed melanins from the pulp fruit of R. echinocarpa presented higher α-glucosidase inhibitory (IC 50 1.00-1.17 mg/mL) activities when compared with acarbose (8.38 mg/mL).…”
mentioning
confidence: 83%
“…Methanolic extracts of Vernonia antihelmitica callus and leaf showed an IC 50 of 0.499 mg/L and 0.372 mg/L, respectively(Rajan et al, 2022). Moderate inhibition (30-50%) of α-amylase is desired since excessive bacterial fermentation of non-digested carbohydrates in colon could cause diarrhea and atulence(Kashtoh & Baek, 2023).Contrasting to the α-amylase activities described above, no enzymatic inhibition was observed for αglucosidase (data not shown). A previous study carried out by Cuevas-Juárez et al(2014), reported that partially puri ed melanins from the pulp fruit of R. echinocarpa presented higher α-glucosidase inhibitory (IC 50 1.00-1.17 mg/mL) activities when compared with acarbose (8.38 mg/mL).…”
mentioning
confidence: 83%
“…This is especially important for people suffering from diabetes type 2, obesity, and lipid peroxidation [93]. Research into plant foods with inhibitory effects on these enzymes is ongoing, with the aim of developing effective interventions for these chronic health conditions [94,95]. Although there are a plethora of data showing the potential of plants to inhibit the activity of these enzymes [96][97][98][99], we were not able to find any dealing with the effect of environmental factors on the ability of plants to inhibit the activity of digestive enzymes, except for our recent one [11].…”
Section: Effects Of High and Low Growing Temperatures On Potential Of...mentioning
confidence: 99%
“…Therefore, it is necessary to undergo further studies to search for new medications that aid in attenuating the progression of the disease and its possible complications (Izzo et al 2021 ). Kashtoh and Baek ( 2023 ) proposed that plant derived drugs with anti-diabetic properties are frequently considered to be cheaper and have low toxicity compared to the other synthetic ones.…”
Section: Introductionmentioning
confidence: 99%